Investitionsanreize im Schienenverkehr. Eine experimentelle Untersuchung. - Ehrmann, Thomas; Hartwig, Karl-Hans; Marner, Torsten; Schmale, Hendrik (Deutscher Verkehrs-Verl., 2006)
Im Mittelpunkt der öffentlichen Diskussion um den avisierten Börsengang der Deutsche Bahn AG steht die Frage, ob das Unternehmen mit oder ohne Schienennetz an die Börse geführt werden soll. Dabei geht es darum, welche Organisationsform die größten gesamtwirtschaftlichen Vorteile generiert. Die möglichen Organisationsformen werden durch den Grad der vertikalen Integration determiniert. difu

With regard to the possible flotation of the DB AG on the stock exchange, discussions are currently focused on a separation - or complete integration - of the rail track network and transport operations plus a range of alternatives. In line with economic theory, a set-up of separate entities may reduce involved parties' interest in investments because of inherent problems over delays, and thus diminish specific welfare enhancing investments targeted at security and innovation. Our experimental review clearly establishes the integration model's superiority among the investment incentives under consideration since the amount of investment, in this case, is likely to reach the social optimum level whereas other alternatives tend to imply severe under investment. The superiority of hybrid model - by comparison with the separate entities model - can nevertheless not be confirmed, a clear indication that the property model cannot be regarded as a hoped-for compromise solution. difu
Keywords: Öffentlicher Verkehr; Schienenverkehr; Eisenbahn; Bahnanlage; Trasse; Infrastruktur; Organisationsform; Verkehrspolitik; Institutionenökonomie; Funktionstrennung; Bahnstruktur; Bahnreform; Börse